2022
DOI: 10.1182/bloodadvances.2020004142
|View full text |Cite
|
Sign up to set email alerts
|

Severe cytokine release syndrome is associated with hematologic toxicity following CD19 CAR T-cell therapy

Abstract: CD19-targeted chimeric antigen receptor (CAR) T-cell therapy has demonstrated remarkable efficacy in patients with relapsed/refractory B-cell malignancies; however, it is associated with toxicities including cytokine release syndrome (CRS), neurotoxicity, and impaired hematopoietic recovery. The latter is associated with high-grade cytopenias requiring extended growth factor or transfusional support, potentially leading to additional complications such as infection or hemorrhage. To date, the factors independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 39 publications
6
84
2
Order By: Relevance
“…If we had a sufficient number of ICANS, it would be reasonable to set up a maximum level of IL-6 beyond which measures were demanded to prevent ICNAS after using Tocilizumab. Severe CRS has been demonstrated to be associated with infections ( 28 , 29 ) which may be related to liver secreting acute inflammatory proteins induced by IL-6 and pancytopenia caused by severe CRS ( 28 ). In our study, patients with elevated CRP over 1.83 times were more likely to develop severe infections after receiving Tocilizumab, which suggested that we should pay more attention to the patients’ infection progression after administration of Tocilizumab and intervene as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…If we had a sufficient number of ICANS, it would be reasonable to set up a maximum level of IL-6 beyond which measures were demanded to prevent ICNAS after using Tocilizumab. Severe CRS has been demonstrated to be associated with infections ( 28 , 29 ) which may be related to liver secreting acute inflammatory proteins induced by IL-6 and pancytopenia caused by severe CRS ( 28 ). In our study, patients with elevated CRP over 1.83 times were more likely to develop severe infections after receiving Tocilizumab, which suggested that we should pay more attention to the patients’ infection progression after administration of Tocilizumab and intervene as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Cytopenia is frequently observed during CAR-T cell therapy and lasts for several days to months, including anemia, thrombocytopenia, and leukopenia, and the incidence of cytopenia range from 30% to 100% in clinical trials (2,29,72,79,142,143). It has been demonstrated that cytopenia is associated with severe CRS (144)(145)(146). Under inflammatory conditions, CD40 is significantly up-regulated on granulocytic progenitor/precursor cells which also express low levels of CD40L, and the CD40/CD40L interactions between granulocytic progenitor/precursor cells significantly promote their own apoptosis (147).…”
Section: Cytopeniamentioning
confidence: 99%
“…While LD chemotherapy can play a role, the etiology is likely multifactorial since hematotoxicty has also been observed in patients who did not receive it (5). High grade CRS has been shown to be associated with delayed hematopoietic recovery (3,4). Other studies show that baseline cytopenias (6) and patients who received prior allogeneic transplants, particularly those who received CAR T-cells less than one year following transplant, were at increased risk (7).…”
Section: Manuscriptmentioning
confidence: 99%